SENSITIVE SOLVATION METHOD FOR SEPARATION SO DETERMINATION OF ZINC(II) AND CADMIUM(II) IN DIFFERENT SAMPLES. - Jawad, Shawket K; Yassin, Manar A (Innovare Journal of Sciences, 2016)
ABSTRACT Objective: Separation and extraction of Zn(II) and Cd(II) as a neutral compound by used methyl stearate as extractant dissolved in chloroform. Methods: Applications of separation and extraction according to solvation method from nitrate aqueous solution by used methyl stearate which is binding coordinally with nitrate salt of metal under study Zn(II) and Cd(II). Results: The extracted species have Î» max =263 nm for Zn 2+ and Î» max =346 nm for Cd . The studies about limitation optimum condition for extraction show 0.3 M salting out effect KNO 3 for Zn 2+ and 0.7 M KNO 3 for Cd 2+ 2+ in present 100 Âµg Zn 2+ /5 ml and 50 Âµg Cd /5 ml with optimum shaking time 15 minutes for both ions. 2+ Conclusion: The separation by solvation method shows high sensitivity and selectivity in addition to high extraction efficiency for separation Zn(II) and Cd(II). As well illustrate the important rule of kind and concentration of salting out agent and different extractions efficiency with differ extractant. Key words: Solvation method, Separation and determination, Zinc(II), Cadmium.